1999
DOI: 10.1074/jbc.274.39.27632
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin A Is a Functional Target of Retinoblastoma Tumor Suppressor Protein-mediated Cell Cycle Arrest

Abstract: Although RB inhibits the G 1 -S transition, the mechanism through which RB prevents cell cycle advancement remains unidentified. To delineate the mechanism(s) utilized by RB to exert its anti-proliferative activity, constitutively active RB proteins (which cannot be inactivated by phosphorylation) or p16ink4a (which prevents RB inactivation) were utilized. Both proteins inhibited the G 1 -S transition, whereas wildtype RB did not. We show that active RB acts to attenuate cyclin A promoter activity, and that ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 55 publications
(116 reference statements)
3
80
1
Order By: Relevance
“…The cDNA expression array demonstrated several genes that were similarly modulated by radiation in both SF188 and normal astrocytes. In both cell types radiation diminished expression of cyclin A, cyclin B1, p55Cdc and DNA topoisomerase II alpha (Table 1), all known to decrease in irradiated or growth arrested cells (Datta et al, 1992;Goswami et al, 1996;Guo et al, 2000;Knudsen et al, 1999;Muschel et al, 1991;Villa et al, 1996;Weinstein, 1997;Weinstein et al, 1998). The cDNA expression array also identi®ed genes that were induced only in primary human astrocytes, expressing wt p53.…”
Section: Tradd Transcription Is Induced By Radiation In Sf188 Cellsmentioning
confidence: 97%
“…The cDNA expression array demonstrated several genes that were similarly modulated by radiation in both SF188 and normal astrocytes. In both cell types radiation diminished expression of cyclin A, cyclin B1, p55Cdc and DNA topoisomerase II alpha (Table 1), all known to decrease in irradiated or growth arrested cells (Datta et al, 1992;Goswami et al, 1996;Guo et al, 2000;Knudsen et al, 1999;Muschel et al, 1991;Villa et al, 1996;Weinstein, 1997;Weinstein et al, 1998). The cDNA expression array also identi®ed genes that were induced only in primary human astrocytes, expressing wt p53.…”
Section: Tradd Transcription Is Induced By Radiation In Sf188 Cellsmentioning
confidence: 97%
“…For all transfections pCMV-b galactosidase was cotransfected to normalize for transfection efficiency. Analysis of luciferase activity was performed 48 h post-transfection as previously described (Knudsen et al, 1999).…”
Section: Rt-pcr Analysis and Reporter Assaysmentioning
confidence: 99%
“…Recently it was shown that BRG-1 is also a component of the RB repressor complex, and is required for RB-mediated inhibition of cyclin A expression, a critical component of the Cdk2 kinase complex (17,18,30). This regulation is significant as cyclin A/Cdk2 expression is required for cell cycle progression (35,36).…”
mentioning
confidence: 99%